Upaya Peningkatan Kemampuan Guru Dalam Menulis Karya Ilmiah (Studi Kasus di SMA Negeri 1 Mojolaban) - Ardinata, Lukhy, Prof. Dr. Bambang Sumardjoko, M.Pd, Dr. Ahmad Muhibbin, M.Si (2016)
The purpose of this study is to describe: 1) the efforts of teachers in improving the ability to write scientific papers; 2) the principals role in improving the teacher ability to write scientific papers; and 3) ability of the teacher in writing scientific papers this time at Mojolaban Senior High School 1. Types the research used in this study is qualitative research to the design of phenomenological. Methods data collection used interviews, observation, and documentation. Data validation was done by triangulation source and techniques. Data analysis used interactive model with the process of data collection, data reduction, data display, and conclusion. Result of this study are: (1) the efforts of teacher to improving scientific papers ability is following scientific papers training by the department of education or university, with MGMP group, teacher to hold the guidance of scientific with PAK team; (2)rincipals role as: a motivator, principal give motivate to teacher to make scientific papers; manager, principals provide an opportunity for teachers to attend trainings and facilitate teacher training fasilitator; and leader, the principal delegate for training teachers either vertically or horizontally; and (3) ability of the teacher in writing scientific papers at Mojolaban Senior High School 1 just a classroom research while other scientific not yet